2021
DOI: 10.3389/fpls.2021.767724
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Metabolomic Analysis Reveals Difference Manufacture Suitability in “Yinghong 9” and “Huangyu” Teas (Camellia sinensis)

Abstract: “Yinghong 9” is a widely cultivated large-leaf variety in South China, and the black tea made from it has a high aroma and strong sweet flavor. “Huangyu” is a light-sensitive tea variety with yellow leaves. It was cultivated from the bud-mutation of “Yinghong 9” and has a very low level of chlorophyll during young shoot development. Due to chlorophyll being involved in carbon fixation and assimilation, the changes in photosynthesis might potentially affect the accumulation of flavor metabolites, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Tissue samples were prepared and carotenoid metabolites were extracted following a previously described method [ 66 ]. Carotenoid contents were quantified using the AB Sciex QTRAP 6500 LC-MS/MS platform from MetWare ( http://www.metware.cn/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue samples were prepared and carotenoid metabolites were extracted following a previously described method [ 66 ]. Carotenoid contents were quantified using the AB Sciex QTRAP 6500 LC-MS/MS platform from MetWare ( http://www.metware.cn/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The flow rate of the mobile phase was 0.35 mL/min; the injection volume was 4 μL. Metabolic compounds identification and quantification were based on the primary and secondary spectral data annotated on MVDB database V2.0 (Metware Biotechnology Co., Ltd., Wuhan, China) and public databases such as MassBank, HMDB, KNAPSAcK, and METLIN [ 15 ]. The orthogonal partial least squares discriminant analysis (OPLS-DA) was carried out using the R package with the identified metabolites [ 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…Researchers accidentally discovered its etiolated bud-mutant, namely ‘Huangyu’. Previous studies have analyzed the differences between the etiolated mutant and ‘Yinghong 9’ in leaf colors, theanine formation, proteomics, and so on, and explained the possible causes of leaf-color variation and the accumulating mechanism of amino acids [ 1 , 15 ]. However, the molecular mechanism of the leaf-color mutation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis, photosynthesis-antenna proteins, and carotenoid biosynthesis are further known to enhance photosynthesis activity in young leaves. Some researchers (37) have suggested that the gradual increase of chlorophyll is involved in carbon fixation, and the photosynthesis would differ from the accumulation of flavor metabolites and the tea quality. Meanwhile, enhanced photosynthesis is also known to facilitate the accumulation of free amino acids and aroma components in tea leaves (6).…”
Section: Transcriptomic Information Of Gylc and Qmlcmentioning
confidence: 99%